Effect of untreated and deep cryotreated tungsten carbide electrodes on PMEDM performance of AISI 304 stainless steel. (21st June 2021) - Bhaumik, Munmun; Maity, Kalipada
Powder mixed electro discharge machining (PMEDM) is the expansion of conventional electro discharge machining (EDM) where powder particles are mixed in the dielectric fluid for acquiring better surface finish and enhancing machining efficiency. Cryotreatment of the electrode is introduced in this study which reduced the tool wear, thus machining cost. In this investigation, SiC powder particles were suspended in kerosene dielectric and the effect of control parameters, cryotreated double tempered (CT2) electrode have been studied on surface crack density (SCD), surface roughness (Ra ), material removal rate (MRR) and tool wear rate (TWR). Powder concentration, duty cycle, pulse on time, peak current, and gap voltage were used as control parameters. EDM operation on AISI 304 stainless steel is performed using untreated (UT) and CT2 tungsten carbide (WC) electrodes. It was found that higher material removal rate and superior surface finish obtained in PMEDM over conventional EDM. CT2 electrode gives less TWR and lesser amount of surface cracks than that of UT electrode.